Non-compaction cardiomyopathy: clinical forms, outcomes and survival in a cohort of belarusian patients - S. M. Komissarova; O. V. Krasko; N. M. Rinejskaya; T. V. Sevruk; A. A. Efimova (Евразийский Кардиологический Журнал, 2022)
The aim is to evaluate the results of long-term follow-up of patients with various clinical forms of NCCM, associated clinical outcomes, as well as 3-year survival.Materials and methods. 211 patients with NCCM (median age 39 [18; 72] years) were examined, of which: 94 (44.5 %) were diagnosed with an isolated phenotype and 117 (55.5 %) with a combination with other cardiomyopathies, including 103 (48.8 %) patients with a combination with DCM; 14 (6.6 %) with HCM, who, in addition to traditional clinical research methods, underwent CMR imaging with late gadolinium enhancement. The endpoints of the study included SCD, SCD with successful resuscitation and implantation of ICD and the implementation of OHT.Results. During the follow–up period (median follow–up 36 [6-211] months), of 211 patients with NCCM, 24 (11.4 %) had adverse outcomes, including 1 (0.5 %) – SCD, 10 (4.7 %) – SCD with successful resuscitation and ICD implantation, 13 (6.2 %) had OHT. SCD occurred in 11 (5.2 %) patients with FC I-II NYHA, including 10 patients with successful ICD resuscitation and implantation after 23 (from 5 to 152) months after diagnosis. OHT was performed in 13 patients with FC III NYHA at 30 (from 8 to 113) months after diagnosis in a group of patients with a combination of NCCM and DCM. The average age at the time of SCD or OHT was 37±12 years.The 3-year survival rate in the group of patients with the isolated form was 98.9 (96.7-100) %, and significantly differed with the group of patients with a combination of NCCM with DCM 86.5 (79.6-94) %, and with the group of patients with a combination of NCCM with HCM 72.9 (50.7-100) %, p=0.0012. Whereas the 3-year survival rate in the group with a combination of NCCM with DCM and NCCM with HCM did not significantly differ from each other. Conclusion. The prognosis of patients with an isolated form of NCCM is generally favorable and their 3-year survival rate was 98.9 (96.7-100) %. The presence of a combination of NCCM with other cardiomyopathies predicts the risk of adverse clinical outcomes and the 3-year survival rate of a combination of NCCM with DCM was 86.5 (79.6-94) %, and when combined with NCCM with HCM 72.9 (50.7-100) %, which may be useful when choosing a management strategy for patients with NCCM.